Structure Re‐determination and Superconductivity Observation of Bulk 1T MoS2. Issue 5 (2nd January 2018) - Fang, Yuqiang; Pan, Jie; He, Jianqiao; Luo, Ruichun; Wang, Dong; Che, Xiangli; Bu, Kejun; Zhao, Wei; Liu, Pan; Mu, Gang; Zhang, Hui; Lin, Tianquan; et al.
Abstract: 2H MoS2 has been intensively studied because of its layer‐dependent electronic structures and novel physical properties. Though the metastable 1T MoS2 with a [MoS6 ] octahedron was observed over the microscopic area, the true crystal structure of 1T phase has not been strictly determined. Moreover, the true physical properties have not been demonstrated from experiments owing to the challenge for the preparation of pure 1T MoS2 crystals. 1T MoS2 single crystals were successfully synthesized and the crystal structure of 1T MoS2 re‐determined from single‐crystal X‐ray diffraction. 1T MoS2 crystallizes in the space group P 3 ‾ m1 with a cell of a=b=3.190(3) Å and c=5.945(6) Å. The individual MoS2 layer consists of MoS6 octahedra sharing edges with each other. More surprisingly, the bulk 1T MoS2 crystals undergo a superconducting transition of T c =4 K, which is the first observation of superconductivity in pure 1T MoS2 phase. Abstract : 1T MoS2 single crystals were successfully synthesized and the crystal structure of 1T MoS2 re‐determined from single‐crystal X‐ray diffraction. The individual MoS2 layer consists of MoS6 octahedra sharing edges with each other. The bulk 1T MoS2 crystals undergo a superconducting transition of T c =4 K, which is the first observation of superconductivity in pure 1T MoS2 phase.